Methods in palaeomagnetism Proceedings of the NATO Advanced Study Institute on Palaeomagnetic Methods, held in the Physics Department of the University of Newcastle upon Tyne, April 1-10, 1964; - Collinson, D. W. (David Wright); Creer, K. M.; Runcorn, S. K. (Developments in solid earth geophysics, 1967)
Methods in Paleomagnetism covers the proceedings of the NATO Advanced Study Institute on Paleomagnetic Methods, held in the Physics Department of the University of Newcastle upon Tyne on April 1-10, 1964. The book focuses on apparatus and techniques used in paleomagnetism and rock magnetism. The selection first offers information on sampling techniques in the field and measurement of natural remanent magnetization. Discussions focus on ballistic and spinner magnetometers; paleomagnetic sampling with a portable coring drill; portable apparatus for collecting small oriented cores; and portable f.